UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SELEDRI (Apium graveolens L) TERHADAP BAKTERI PSEUDOMONAS AERUGINOSA SECARA IN VITRO - Wahyuni Sihombing; Muhammad Yunus; Edy Fachrial (Universitas Imelda Medan, 2026)
Celery leaves (Apium graveolens L) are plants with various properties according to people's beliefs, one of which is functioning as an antibacterial for skin infections. The skin on the largest human body organ located on the external part of the body whose function is to protect the body parts underneath. This skin disease is caused by bacteria, namely Pseudomonas aeruginosa bacteria, this bacteria is a gram-negative bacteria. The purpose of this study was to determine the effectiveness of celery leaves (Apium graveolens L) against pseudomonas aeruginosa bacteria In Vitro, with concentrations of 2.5%, 5%, 7.5%, 10%, 15%, 20%. In the negative control using 10% DMSO solution, and in the positive control using chloramphenicol disk This study is an experimental study. The research method uses the maceration method using 96% ethanol solvent, sterilization of tools, bacterial rejuvenation, media preparation, test solution preparation, and measurement of inhibition zones after incubation for 24 hours at 37 ° C. The results of this study showed that celery leaf extract (Apium graveolens L.) could inhibit bacterial growth at all tested concentrations. The conclusion is that celery leaf extract (Apium graveolens L) is effective in inhibiting bacterial growth.